A Book for None? Teaching Biblical Studies to Millennial Nones. (19th May 2016) - Reed, Randall
Abstract: The millennial generation is distinctive for several reasons, not the least is its growing religious disaffiliation. Given a growing disinterest in religion in general and the Bible in particular especially among the fast growing group of millennial "nones" how can biblical studies classes still be seen as appealing and relevant? This article seeks to answer this question by examining the identity and concomitant values of millennials. As a result of this analysis I argue that while the Bible as inherent authority may be quickly losing its appeal, the Bible as an example of human creativity, group reflection, political rhetoric, and social discourse makes the study of the Bible particularly relevant for millennials contemplating careers in the global marketplace even if the importance of the Bible itself is waning for this generation. I show how in my introductory New Testament class I attempt to implement these ideas.